YOShLARNI AXLOQIY-ESTETIK TARBIYALAShNING PSIXOLOGIK OMILLARI - Abdimuratov, J. (SCIENCE and SOCIETY, 2025)
The article examines the psychological factors of moral and aesthetic education of youth, the requirements of national mentality and the national model of education, self-education, self-control, and the levels of social and moral phenomena in the life of adolescents